Exploring the Religious Identity of Dalits through the Lens of Religious Conversion - Ayub, Afsara (Vilnius University Open Series, 2025)
The paper examines the role of religion among Dalits in India, especially focusing on Dalit religious conversion from Hinduism to Buddhism. It is based on a case study of Dalit conversion in Shabbirpur village in the Northern Indian state of Uttar Pradesh. In line with the existing research on Dalit conversions, this paper shows that Dalit conversion in Shabbirpur serves not merely as a religious but also as a political and social strategy of Dalits through which they try to negotiate their caste identity. For Dalits, conversion means a resistance to caste oppression as well as assertion of divergent religious identity from the majoritarian Hindu identity. While exploring the Dalit religious identity following their conversion in Shabbirpur, the paper challenges the prevailing notion that religious conversion simply denotes a transfer of religious affiliation. Instead, it elucidates that Dalit religious conversion is a social process wherein Dalits’ transition from one religion to another devoid of a fundamental spiritual transformation. Through this case study, I argue that there exists a continuation of the past and present spiritual affiliation which involves hybridization of religious practice, fusing worship of Ravidas with a new Buddhist identity. Interestingly, this syncretization is not unintentional. It is a conscious attempt to keep both pre-and post-converted religious traits as part of their re-invented socio-religious identity.